Empowering Tofu and Tempe Craftsmen to Improve Sustainable Local Economy in Lohbener Village, Lohbener District, Indramayu Regency - casri, Casriyanti (Kusuma: Jurnal Pengabdian kepada Masyarakat, 2024)
This co mmunity service activity aims to increase the capacity of tofu and tempeh craftsmen in order to improve their economic welfare in a sustainable manner. This program includes business management training, product diversification, marketing strategy development, and production waste management. The methods used include socialization, direct mentoring, and evaluation of activity results. The results obtained show an increase in the knowledge and skills of craftsmen in business management, increased income, as well as efforts to manage waste that is more environmentally friendly.